FOLIAR FERTILIZER APPLICATION: EFFECTS ON AGRONOMIC PERFORMANCE AND ESSENTIAL OIL PROFILE ACROSS DIFFERENT MENTHA SPECIES - Mehmet Fatih ÇAKIR (Journal of Animal and Plant Sciences, 2025)
This study investigated the effects of various foliar organic fertilizers (plant-based amino acid, animal-based amino acid, and seaweed extract) on the agronomic performance and essential oil composition of commercially important Mint (Mentha) plant species: Mentha arvensis, Mentha × piperita, and Mentha spicata. The experiment was laid out under randomized complete block design (RCBD) with three replications during the 2021 and 2022 growing seasons. Significant variations in dried leaf yield, essential oil content, and composition have been observed among the mint species used in the study and the different foliar fertilizer treatments. Species × fertilizer combinations exhibited improvements in the examined traits compared to species × control applications, dried leaf yield from 14.17% to 32.14%, and essential oil content from 7.72% to 17.79%. The essential oil composition exhibited notable variations depending on the species. The menthol content ranged from 58.75% to 66.29% in Mentha arvensis, from 30.40% to 52.23% in Mentha×piperita (Mitcham, Multimentha, Swiss), and carvone varied between 31.70% and 44.12% in Mentha spicata. Pearson correlation analysis revealed significant positive correlations among yield traits and a strong correlation between essential oil content and essential oil yield. Principal component analysis (PCA) explained 97.4% of the total variance and clearly separated Mentha species × fertilizer combinations based on agronomic performance, essential oil content, and yield. Mentha arvensis × fertilizer combinations excelled in essential oil content and yield, while Mentha × piperita Multimentha × fertilizer combinations excelled in agronomic traits. The highest essential oil yield was obtained from Mentha arvensisΧ T3 combination, while the highest dried leaf yield was recorded for Mentha × piperita Multimentha Χ T4 combination. These findings emphasize the necessity of selecting appropriate mint species and foliar fertilizer treatments to optimize yield and essential oil quality, thereby enhancing the economic potential of mint cultivation.
Keywords: Mentha; foliar fertilizer; agronomic traits; yield; essential oil; multivariate analysis